2011
DOI: 10.1128/jcm.01186-11
|View full text |Cite
|
Sign up to set email alerts
|

Viral-Bacterial Interactions and Risk of Acute Otitis Media Complicating Upper Respiratory Tract Infection

Abstract: Acute otitis media (AOM) is a common complication of upper respiratory tract infection whose pathogenesis involves both viruses and bacteria. We examined risks of acute otitis media associated with specific combinations of respiratory viruses and acute otitis media bacterial pathogens. Data were from a prospective study of children ages 6 to 36 months and included viral and bacterial culture and quantitative PCR for respiratory syncytial virus (RSV), human bocavirus, and human metapneumovirus. Repeated-measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
132
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(140 citation statements)
references
References 37 publications
(68 reference statements)
3
132
2
3
Order By: Relevance
“…Preceding or concurrent viral upper respiratory tract infection is typical in AOM (10), and interactions of viruses and bacteria in the nasopharynx may play an important role in the pathogenesis of AOM (10)(11)(12). In the era of increasing antimicrobial resistance, precise information concerning MEF pathogens may be beneficial for empirical antibiotic therapy, and therefore PCR technique applied to samples from this primarily sterile site may help to achieve more-accurate bacterial etiologic diagnosis of AOM.…”
Section: B Acterial Culture Of Middle Ear Fluid (Mef) Has Been the Stmentioning
confidence: 99%
“…Preceding or concurrent viral upper respiratory tract infection is typical in AOM (10), and interactions of viruses and bacteria in the nasopharynx may play an important role in the pathogenesis of AOM (10)(11)(12). In the era of increasing antimicrobial resistance, precise information concerning MEF pathogens may be beneficial for empirical antibiotic therapy, and therefore PCR technique applied to samples from this primarily sterile site may help to achieve more-accurate bacterial etiologic diagnosis of AOM.…”
Section: B Acterial Culture Of Middle Ear Fluid (Mef) Has Been the Stmentioning
confidence: 99%
“…4, we explored protection in an in vivo model that mimics the clinical progression of pneumococcal disease onset. Epidemiological evidence suggests that pneumococcal disease is strongly associated with a concomitant infection with upper respiratory tract viruses, such as influenza A virus (IAV) (40,41). Mice were infected intranasally with IAV 48 h after colonization with S. pneumoniae, a protocol designed to mediate the release of virulent pneumococci from colonizing biofilms for subsequent dissemination to the lungs and blood.…”
Section: Directed Response and Extended Coverage Provided By Combinedmentioning
confidence: 99%
“…Other studies have revealed that PspA, when employed as an immunogen in mouse models, protects against primary pneumococcal infection (20-23) and against pneumococcal challenge subsequent to a viral infection (24,25). The vast majority of these investigations, however, examined the protection offered by PspA immunization against invasive disease caused by challenge with planktonic, broth-grown pneumococci, which do not represent either the biofilm community of S. pneumoniae normally found residing in the nasopharynx prior to contact with IAV or the bacteria released from biofilms in response to virus infection (4). Thus, the capacity of PspA, when used as an immunogen, to protect against invasive disease produced by pneumococci that are residing in a commensal nasopharyngeal biofilm subsequent to infection with IAV and its protective role against pneumonia and otitis media have not been adequately evaluated.…”
mentioning
confidence: 99%
“…One of the most important of these biological pairings is the interaction between influenza A virus (IAV) and Streptococcus pneumoniae (the pneumococcus) (2). In children, the most frequent complication following IAV infections is acute otitis media, of which S. pneumoniae is one of the most common etiologic agents (3)(4)(5). S. pneumoniae is also the most frequently identified pathogen in hospitalized children and adults who present with primary or secondary community-acquired pneumonia (6).…”
mentioning
confidence: 99%